Women and human rights - "Pachauri, S. K." (New Delhi, 1999)
This book contains Violence against Women, Status of Women, Crime against Women, Rape A Horrendous Crime, Women Prisoners, Role of Divorce, Modern Women, Dowry Deaths A National Shame etc.
Keywords: Women